Effects of different protocols of high intensity interval training for VO2max improvements in adults: A meta-analysis of randomised controlled trials. Issue 8 (August 2019) - Wen, Daizong; Utesch, Till; Wu, Jun; Robertson, Samuel; Liu, John; Hu, Guopeng; Chen, Haichun
Abstract: Objectives: To examine the effects of different protocols of high-intensity interval training (HIIT) on VO2 max improvements in healthy, overweight/obese and athletic adults, based on the classifications of work intervals, session volumes and training periods. Design: Systematic review and meta-analysis. Methods: PubMed, Scopus, Medline, and Web of Science databases were searched up to April 2018. Inclusion criteria were randomised controlled trials; healthy, overweight/obese or athletic adults; examined pre- and post-training VO2 max/peak; HIIT in comparison to control or moderate intensity continuous training (MICT) groups. Results: Fifty-three studies met the eligibility criteria. Overall, the degree of change in VO2 max induced by HIIT varied by populations (SMD = 0.41–1.81, p <  0.05). When compared to control groups, even short-intervals (≤30 s), low-volume (≤5 min) and short-term HIIT (≤4 weeks) elicited clear beneficial effects (SMD = 0.79–1.65, p <  0.05) on VO2 max/peak. However, long-interval (≥2 min), high-volume (≥15 min) and moderate to long-term (≥4–12 weeks) HIIT displayed significantly larger effects on VO2 max (SMD = 0.50–2.48, p  < 0.05). When compared to MICT, only long-interval (≥2 min), high-volume (≥15 min) and moderate to long-term (≥4–12 weeks) HIIT showed beneficial effects (SMD = 0.65–1.07, p  < 0.05). Conclusions: Short-intervals (≤30 s), low-volume (≤5 min) and short-term (≤4 weeks) HIIT represent effective and time-efficient strategies for developing VO2 max, especially for the general population. To maximize the training effects on VO2 max, long-interval (≥2 min), high-volume (≥15 min) and moderate to long-term (≥4–12 weeks) HIIT are recommended.